Effects of self-compassion on aggression and its psychological mechanism through perceived stress - Fang Guan; Chengqing Zhan; Shanyin Li; Song Tong; Kaiping Peng (BMC Psychology)
Abstract Given the increasing global concerns about aggressive behaviors and the pressing need for effective psychological interventions, this study delves into the potential of a concept deeply rooted in positive and Buddhist psychology but largely researched in Western contexts, as a mitigating factor against aggression in Chinese adults. Through three core studies involving 652 participants (age: 30.52±8.16), our research illuminated the intricate relationship between self-compassion, perceived stress, and aggression. Study 1 identified a negative correlation among these variables, setting the empirical foundation. In Study 2, participants exposed to a self-compassion exercise reported enhanced self-compassion and reduced aggression. Study 3 further consolidated these findings, with participants in the self-compassion writing group, showing notable increases in self-compassion and decreases in aggression compared to a control group. Critically, perceived stress emerged as a significant mediator between self-compassion and aggression, elucidating its central role in this dynamic. Together, our findings underscore the promise of self-compassion as a strategy to curb aggression tendencies, especially in light of its influential relationship with perceived stress, suggesting vital implications for future mental health interventions.